Unearthing Love on the Central Australian Frontier - Wells, Linda (SARE: Southeast Asian Review of English, 2019)
This story centres around a tin shed known as the Bungalow that was built in Alice Springs in 1914 to house Topsy Smith, an Indigenous Arabana woman, and her seven children. Topsy’s husband, Welsh-born Bill Smith, had died at the mines. Topsy lived in the Bungalow for the next fifteen years, raising her own children as well as about forty other “half-caste” children, who had been taken from their families in the surrounding desert lands. I am the white Australian mother of a mixed-heritage Indigenous daughter and have lived for nearly three decades in Central Australia. My aim, through this piece, is to create a post-colonial, literary reimagining of the story of the Bungalow, using techniques of speculative biography, archival poetics, ekphrasis and auto-ethnography. Part of my doctoral research, this paper explores how I have used methodologies of practice-led research and creative non-fiction to reimagine Topsy Smith’s life and come to see her, not as a shadowy and little known figure of history but as a woman full of life and love. My supervisors encourage me to interrogate my motivation for this topic. I offer intellectual, political and personal explanations, but still they prod. I dig further to arrive at my own core provocation of love.